Microstructural and mechanical properties of porous Si3N4 carbon coated ceramic brazed with a cobalt-silicon filler. Issue 10 (August 2017) - Zhuang, Y.L.; Lin, T.S.; Wang, S.J.; He, P.; Sekulic, D.P.; Jia, D.C.
Abstract: The Co22.5 Si77.5 (at.%) braze was used to bond porous Si3 N4 ceramics. The effects of brazing temperature on microstructure and the bonding strength of the joint were studied. The results reveal that no visible reaction layer was observed. The corresponding joint strength was low. In order to improve the joint strength a carbon coated modification of the porous Si3 N4 substrate was suggested. The impact of this modification on the joint properties was examined. It was established that a SiC reaction layer with a thickness from ∼15 μm to ∼65 μm was formed at the interface and SiC nanowires were observed when the temperature increased from 1280 °C to 1340 °C. The maximum shear strength of the carbon coated and uncoated joints were 115 MPa and 44 MPa, respectively. The significant improvement of the joint strength was attributed to the SiC reaction layer and a strengthening by the presence of SiC nanowires. .